Shortening Tendency for Syllable Duration in Brazilian Portuguese Utterances. Issue 2 (3rd April 2018) - Rothe-Neves, Rui; Bernardo, Bárbara Marques; Espesser, Robert
Abstract: We investigated whether the mean duration of syllables in utterances of different length in Brazilian Portuguese conform to Menzerath–Altmann's law. Furthermore, by analysing the same spoken material of twenty recorded speakers, we tested for individual differences in the parameters used to formalise the law. The log-transform of the syllable duration was the dependent variable in a linear mixed model with the log-transform of the number of syllables in the utterance as a predictor. Adding a random intercept accounted for the variability across the speakers, but a random slope by speaker did not improve the model. We conclude that Menzerath–Altmann's law fits our data well, but the decreasing tendency is not different from speaker to speaker.